Pengaruh Brand Personality terhadap Loyalitas Nasabah Pengguna Aplikasi LIVIN by MANDIRI pada PT BANK MANDIRI (PERSERO) TBK - Antyo Pracoyo; Cecilia Malona (STIE Indonesia Banking School, 2023)
The purpose of this research is to determine the dimension of Responsibility, Agility, Courage, Simplicity, and Emotionally on Brand Personality which have a significant influence on customer loyalty using Livin by Mandiri application at PT. Bank Mandiri (Persero) Tbk. Data obtained from 241 respondents who are customers of PT. Bank Mandiri (Persero) Tbk. The results show that from 5 variables there are 3 of them that give a positive influence and 2 other variables do not have an effect on customer loyalty. The Responsibility variable, Courage variable, and Emotionaly variable have a positive influence on customer loyalty, while the Agility variable and Simplicity variable have no positive effect on customer loyalty.